2023
DOI: 10.3389/fcvm.2023.1063562
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of remnant cholesterol level for all-cause mortality in heart failure patients

Abstract: BackgroundLower cholesterol levels are associated with increased mortality in heart failure (HF) patients. Remnant cholesterol corresponds to all cholesterol not found in high-density lipoprotein (HDL) and low-density lipoprotein (LDL). The prognostic role of remnant cholesterol in HF remains unknown.ObjectiveTo reveal the relationship between the baseline remnant cholesterol level and all-cause mortality in HF patients.MethodsThis study enrolled 2,823 patients hospitalized for HF. Kaplan–Meier analysis, Cox r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…included 3,403,414 community-based participants from ChinaHEART, an ongoing government-funded public health program throughout China. They found that the second percentile levels of RC concentrations were associated with the lowest all-cause mortality ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…included 3,403,414 community-based participants from ChinaHEART, an ongoing government-funded public health program throughout China. They found that the second percentile levels of RC concentrations were associated with the lowest all-cause mortality ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…На початку 2000 років з'явилися дані щодо кращого клінічного перебігу й виживаності хворих на ожиріння та хронічну серцеву недостатність (ХСН) [1,3,7,15,20] порівняно з недостатньою, надлишковою та нормальною масою тіла незалежно від фракції викиду лівого шлуночка (ФВ ЛШ) [2,4,5,17,21]. Дослідники визначили це як «парадокс ожиріння», або «зворотну епідеміологію» [4].…”
unclassified
“…Продовження вивчення парадоксу ожиріння з відкриттям надалі «парадоксу холестерину» [5,25], коли нижчі показники всіх видів холестерину супроводжувались тяжчим перебігом і наслідками ХСН, сприяло розвитку теорії «зворотної епідеміології» [6,7,8,9]. Нині ХСН визначають як «зворотний метаболічний синдром» [10], що має такі компоненти: системна та локальна міокардіальна інсулінорезистентність; мітохондріальна дисфункція; втрата маси тіла, що прогресує та в термінальному періоді ХСН спричиняє настання «кардіальної кахексії»; міокардіальна енергетична недостатність внаслідок пригнічення метаболізму ліпідів, що зумовлює перехід від жирних кислот до глюкози як основного енергетичного субстрату з наступним зниженим окисним фосфорилюванням і порушенням утворення АТФ [6,10,11].…”
unclassified
See 2 more Smart Citations